Design of experiment for evaluating the optimal condition in drying process of rubberwood - Kaewploy, Somsak; Boonseng, Kulyuth (Asia-Pacific Journal of Science and Technology, 2017)
This research work aimed to evaluate the optimal condition in drying process of rubberwood that had been applied in lumber trade of rubberwood. The design of experiment approach and result analysis by applying the Minitab program of version 16 were applied in the present study. The study factors affecting on % moisture content as standard required were temperature, time and open-close damping in drying process. In the present experiment, the material was 2 inch-thickness rubberwood through a fumigation process. After applying experimental design of completely general factorial model, It was found that the factors of temperature and time in drying, affected on the wood moisture significantly statistic. After that, the optimal drying condition of rubber wood was evaluated by applying Box-Behnken Design. The analytical result concluded that regression equation of drying condition of rubberwood was % moisture content = 343.640 – 0.788A – 42.464B + 1.339B 2+ 0.053AB which derived from analysis of reliable data in 8- 12% limited moisture content range.